The Austral Predator Katydid—new species of Megatympanon Piza, 1958 (Orthoptera: Tettigoniidae: Listroscelidinae: Terpandrini) from the Brazilian Atlantic Rainforest - Mendes, Diego Matheus De Mello; Sobral, Rafael; Neto, Alberto Moreira Da Silva (Zootaxa, 2023)
Megatympanon Piza, 1958 (Tettigoniidae: Listroscelidinae: Terpandrini) is presently a monotypic genus and the only Terpandrini occurring in South America. The type-species M. speculatum Piza, 1958 is recorded in the Atlantic Forest biome in southeastern Brazil. In this work, we describe an additional species, Megatympanon austroraptorum sp. nov., the second species of the genus, occurring in the Southern Atlantic Forest biome. The new species is described based only on a single male; the female of the new species is unknown. A distribution map of the genus is provided as well as comments on the natural history of the new species.